PENGARUH LEVERAGE, PROFITABILITAS, DAN LIKUIDITAS TERHADAP INDIKASI ADANYA KECURANGAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024) - Natasya Kayla Najla; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2026)
This study aims to examine the influence of Leverage, Profitability, and Liquidity on Indications of Financial Statement Fraud of manufacturing companies listed on the Indonesia Stock Exchange in 2022-2024. This study refers to fraud triangle theory.The population used in this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Purposive sampling was used in selecting the research sample, resulting in 430 research samples for three consecutive years (2022-2024).The analysis results show that Leverage have a positive and significant effect on Indications of Financial Statement Fraud, and Profitability also has a positive and significant effect on Indications of Financial Statement Fraud. Additionally, it was found that Liquidity do not have a significant direct effect on Indications of Financial Statement Fraud.